Wind Flow Simulation around Rhizophora Mangrove Roots Using Computational Fluid Dynamics. (5th May 2022) - Rahuman, Sini; Ismail, A. Mohamed; Varghese, Shyla Manavalan; Toworfe, George Kwamina; Sasikumar, Bashyam
Abstract : The characteristics of Rhizophora mangrove root structures and its efficiency in velocity dissipation process of heavy wind are studied in this paper. The influence of Rhizophora Mangrove roots on severe tropical storm (88 -117 km/hr.), intense tropical cyclone (166-212 km/hr.), and very intense tropical cyclone (above 212 km/hr.) is investigated by simulating wind flow around these roots with inlet velocities 100 km/hr., 200 km/hr., and 300 km/hr. ANSYS Fluent software is used for developing the computational fluid dynamic (CFD) model and to perform simulation and analysis. The flow velocity profile reveals that these mangrove root structures have a significant impact on the severe and intense wind flow. It is found that the Rhizophora root structures reduce the velocity of the wind by more than 80% of the inlet velocity. This information can be utilized to visualize and better understand the benefits of these root structures and to reestablish mangrove forest, create new breakwater models, and to strengthen the existing ones.